Evaluation of In vitro Anthelmintic Activity, Total Phenolic Content and Cytotoxic Activity of Crinum latifolium L. (Family: Amaryllidaceae) - Abdul Aziz; Golam Sarwar Raju; Abhijit Das; Jamiuddin Ahmed; Md. Mizanur Rahman Moghal (Tabriz University of Medical Sciences, 2014)
Purpose: Crinum latifolium is a widely used plant in Asian folk and traditional medicine.In the present study, we have tried to find out the anthelmintic activity, total phenolic contents and cytotoxicity of the methanolic extract of the target plant. Methods: Anthelmintic activity was assessed applying five different concentrations of the plant extract and recording the time of paralysis and death. Total phenolic contents were determined using Folin-Ciocaltu method, using Gallic acid as standard; while brine shrimp lethality test (BSLT) method was used to evaluate the cytotoxicity of the plant extract, where vincristine sulphate and DMSO was used as positive and negative control respectively. Result: The lowest time for paralysis and death of worms, for test sample at highest concentration (50mg/ml), were found 24±0.45 and 46.4±0.60 min respectively, which gradually increased with the decrease of concentration. On the other hand, albendazole, which was used as standard, caused paralysis and death of worms at 56.2±0.20 min and 77.4±0.24 min respectively; whereas no mortality of the worms was observed, when distilled water was used as control. The crude methanolic extract exhibited lower amount of total phenolic content (17.50±2.64 mg/ml). In case of cytotoxicity measurement, the crude methanolic extract showed positive result (with LC50 15.652 µg/ml) compared to standard Vincristine sulphate (0.839 µg/ml); which indicated that the leaves of Crinum latifolium possess mild cytotoxic principles. Conclusion: Therefore, further studies are suggested to evaluate the possible mechanism of action and the active compounds responsible for the biological activities of the plant extract.